Pemanfaatan Tayangan Youtube Sebagai Media Konseling Mental Siswa Di Madrasah Aliyah Persiapan Negeri Besitang - Wahyu Ziaulhaq (ASIAN PUBLISHER, 2023)
This study describes the use of YouTube broadcasts as a medium for mental counseling for students at the Besitang Negeri Bestang Preparatory Madrasah Aliyah. The purpose of this research is to educate readers that during the Covid-19 pandemic, learning activities were not carried out face-to-face, but made use of video shows to break the chain of transmission of Covid-19, then the video shows were watched by students at home, and students were given assignments by the teacher. The research method used is qualitative. The approach used is an anthropological and sociological approach. Data collection techniques are through observation and unstructured interviews. After the data is obtained, the data is analyzed scientifically. The results of the research that have been found show that First, video shows are the right media to be used as a source of teaching materials for the masses of Covid 19 so students can study at home through these video shows. Second, video shows are packaged in language that students can easily understand with a duration of around thirty minutes. Third, video shows are packaged with an attractive appearance that contains teaching material content.